Kajian Sosiologi Sastra Dalam Cerpen “Di Persimpangan Pantura” Karya Tantri Pranash - Eny Junyanti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A short story is a literary work in the form of prose that contains a conflict with a short, focused solution only on one incident or story. The most important thing in a short story is to reveal the author's events and ideas in such a way that the reader can understand and enjoy it. The short story